EFEKTIVITAS PENGGUNAAN METODE NUMERIK DALAM MENENTUAN TEGANGAN KERJA DIODA - Djeli Tulandi (Charm Sains: Jurnal Pendidikan Fisika, 2020)
Working voltage diode can be determined based on the exponential form equation that states the relationship between the variable electrical current , voltage , and temperature diode electron charge . Determination of potential voltage diode can be done numerically using the method of looking for the root of the equation . There are several methods of searching for the roots of the equation graph method , the direct method , the two methods , regulation falsi method , Newton – Raphson method and the secant method.The purpose of this study is to show which method is most effective in determining the working voltage diode . The method used is descriptive analytic method . The results showed that the direct measurement method is a short procedure , obtain employment diode voltage v = 0.42216 volts at the 4th iteration , as well as the method of Newton - Raphson procedure is also very short because it only took 5 steps in determining the working voltage diode . The other method , the method for two , regulations falsi and secant method requires a longer iteration. Themethod is effective in determining the working voltage of diode 5selected method I sadirectmethod an dNewton-Raphson method